Differential impact of spotted fever group rickettsia and anaplasmosis on tick microbial ecology: evidence from multi-species comparative microbiome analysis - Jin-qi Wang; Tian Yu; Hong-yu Qiu; Sheng-wei Ji; Zhi-qiang Xu; Qi-chao Cui; Hai-feng Li; Wan-feng Liang; Shuai Feng; Chen-tao Fu; Xu Gao; Zhen-zhen Han; et al. (Frontiers in Microbiology)
Tick-borne diseases (TBDs) pose a significant public health challenge, as their incidence is increasing due to the effects of climate change and ecological shifts. The interplay between tick-borne pathogens and the host microbiome is an emerging area of research that may elucidate the mechanisms underlying disease susceptibility and severity. To investigate the diversity of microbial communities in ticks infected with vertebrate pathogens, we analyzed the microbiomes of 142 tick specimens. The presence of Rickettsia and Anaplasma pathogens in individual samples was detected through PCR. Our study aimed to elucidate the composition and variation of microbial communities associated with three tick species, which are known vectors for various pathogens affecting both wildlife and humans. We employed high-throughput sequencing techniques to characterize the microbial diversity and conducted statistical analyses to assess the correlation between the presence of specific pathogens and the overall microbial community structure. Pathogen screening revealed an overall positivity rate of 51.9% for Anaplasma and 44.6% for spotted fever group rickettsia (SFGR). Among the three tick species (Dermacentor silvarum, Haemaphysalis concinna, and Haemaphysalis japonica) analyzed, D. silvarum (the predominant species) exhibited the highest pathogen prevalence. The results indicate significant variation in microbial diversity between tick samples, with the presence of Anaplasma and SFGR associated with distinct changes in the microbial community composition. These findings underscore the complex interactions between ticks and their microbial inhabitants, enriching our understanding of tick-borne diseases.